Equity Pedagogy di Pesantren Dirasatul Mualimin Islamiyah Al-Hamidy Banyuanyar - Syaiful, Ach.; Mukhtar Harahap, Radinal; Rahman, Mufiqur (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
One of the dimensions of multicultural education is the dimension of Equity Pedagogy or justice and equality in receiving learning. The educational culture of Islamic boarding schools that is centralized to Kyai poses a challenge to how pesantren provide equity education services to students through the learning system in it. This study aims to identify the value of equity pedagogy in the type of traditional pesantren (salaf) with a phenomenological approach, the results of this study indicate that the Banyuanyar pesantren has a culture of Equity Pedagogy values ​​such as equity in Kyai policies, equity in Nyabis culture, equity in Discipline culture, equity in living culture mutual tolerance (mutual tolerance). equity in the culture of living together (help each other). equity in the culture of living tawashi (reminding each other). A culture of equal living that is fair in the context of gender